Pengaruh E-Service Quality dan Brand Image Terhadap Continuance Usage Intention Platform DANA Dompet Digital oleh Generasi Y dan Z - Ayuni, Ayuni; Amanda, Siti Nabillah Suci; Yusuf, Abdul (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
The purpose of this study is to test whether E-Service Quality and Brand Image affect the Continuance Usage Intention of the DANA Dompet Digital Indonesia Platform. This study uses quantitative research, the population of this study is the users of DANA Dompet Digital Indonesia. The research data was collected through a questionnaire with a sample of 100 respondents consist of 73 women and 27 men respondents using non-probability sampling (purposive sampling) is a sampling technique based on certain considerations that are considered to represent, a population with the categories of generations Y and Z in the age range of 17-40 years and majority respondents are university students. Data were analyzed using SPSS 25 and SmartPLS 3.0. The results showed that E-Service Quality had a significant effect on the Continuance Usage Intention of the DANA Dompet Digital platform and Brand Image had a significant effect on the Continuance Usage Intention of DANA Dompet Digital.